Analysis of estrogens and estrogen mimics in edible matrices—A review. Issue 8 (7th March 2014) - Adamusova, Hana; Bosakova, Zuzana; Coufal, Pavel; Pacakova, Vera
<x xml:space="preserve">Abstract</x> This review provides a brief survey of the biological effects of selected endocrine‐disrupting compounds that are formed after internal exposure of organisms. Further, the present analytical methods available for the determination of these compounds in foodstuffs are critically evaluated. The attention is primarily devoted to the methods for sample pretreatment, which are the main source of errors and are usually the most time‐consuming step of the whole analysis. This review is focused on selected natural and synthetic estrogens, estrogen conjugates, and chemical additives used in the plastic industry that can act as estrogen mimics.